The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-11371-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal activation energy of 3D vortex matter in NaFe1−x Co x As (x = 0.01, 0.03 and 0.07) single crystals

Abstract: We report on the thermally activated flux flow dependency on the doping dependent mixed state in NaFe1−xCoxAs (x = 0.01, 0.03, and 0.07) crystals using the magnetoresistivity in the case of B//c-axis and B//ab-plane. It was found clearly that irrespective of the doping ratio, magnetoresistivity showed a distinct tail just above the T c,offset associated with the thermally activated flux flow (TAFF) in our crystals. Furthermore, in TAFF region the temperature dependence of the activation energy follows the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…In order to understand the pinned vortex liquid phase under magnetic field in superconducting SmBCO-coated conductors, we would like to analyze the significantly broadening electrical resistivity resulting from the thermally activated flux flow for the vortex. According to TAFF theory, if the applied current density in the TAFF region is not large, the electrical resistivity is expressed as follows [26][27][28][29] :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the pinned vortex liquid phase under magnetic field in superconducting SmBCO-coated conductors, we would like to analyze the significantly broadening electrical resistivity resulting from the thermally activated flux flow for the vortex. According to TAFF theory, if the applied current density in the TAFF region is not large, the electrical resistivity is expressed as follows [26][27][28][29] :…”
Section: Resultsmentioning
confidence: 99%
“…This result helps to understand the vortex movement more accurately. Actually, in order to consider the temperature dependence of the prefactor ρU T 2 / c , the introduction of the nonlinear relationship of U T H ( , ) vs. T has been performed in many cuprates and iron-based superconductors 23,29,30,32 . Using the nonlinear relationship are derived.…”
Section: Resultsmentioning
confidence: 99%
“…For magnetic fields perpendicular to the ab layers it readswhere is the polygamma function, , is so called Lawrence-Doniach parameter, S is the interlayer distance, and c is the total-energy cutoff constant that corresponds to ε -value at which Δ σ vanishes. To compare with the experimental data, we used T c  = 16.3 K (as determined from the analysis of the critical region), c  = 0.5 (according to the ε -value at which at which fluctuation effects vanish), and s  = 0.74 nm 42 . As it is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After completion of heat treatment, typical dimensions of as-grown single crystals are 0.1 × 1 × 2 mm 3 for almost each of the three series of samples. We used single crystals from the same batches used in our recent paper 42 . During this study, XRD analyses revealed well defined (0 0  l ) peaks with FWHM of about 0.05°.…”
Section: Methodsmentioning
confidence: 99%
“…Following the treatment for different kinds of superconductors 9 , 41 43 the ac susceptibility data gives us the vortex activation barrier within the framework of the thermally activated vortex motion model. The insets to Fig.…”
Section: Discussionmentioning
confidence: 99%